Antibiotic-loaded polylactic acid fibers for the treatment of skin infections - ULAĞ, SONGÜL (My University, 2023)
Skin infections are medical conditions caused by parasites, bacteria, viruses and fungi when these microorganisms enters skin by having damaged skin or simply with insect bite, mostly skin infections can be recognized with edema, erythema, lesions and other inflammation signs [1] Globally according to systemic study covered skin diseases analysis between 1990 and 2019 the number of bacterial skin diseases patients is increasing with rate of change of age standarized (7.38%) [2], this study raised the awarness about finding ways to prevent the formulation of skin infections and treating it in effective way. Traditional methods in treating skin infections includes the herbal treatments that were used form ancient centuries (e.g. Achyranthes aspera , Aloe vera,...), these herbs have proved its effectivness with more than 80% cured people in India which depends on traditional treatments for skin diseases [3]. Conventional treatment of skin infections includes the usage of antibiotics in its different forms, and different mechanism of action according to the cause of the infection (gram positive or gram negative bacteria). On the other hand, the dosage differ according to the form of antibiotics, and the antibiotic type[4] Modern medicine of treating skin infections includes the usage of new drug delivery systems which applies the usage of biomaterials (polymers, ceramics, metals, composites) at different size scales (macro, micro, nano) that help in reducing the side effects of drugs, extend the half-life, and having optimal pharmacokinetics processes for the targeted drug [5]. In the last two decades, the interset in developing new methods to deliver drugs has become more and more; espically the deliver of antibiotics because of the increase in resistance on global scales. These methods includes using different techniques such as electrospinning technique which produces fibers mainly composed of polymers loaded with drugs, this technique is classified as promising method for personlized medicine and the improvement of drug release profiles. [6] In this work, we tried to focus on taking advantages of electrospinning technique to deliver minimum amount of antibiotics (Gentamicin, Caffeic Acid) to skin for the treatment of skin infections away from antibiotic resistance. Fibers were fabricated by loading antibiotics with Poly Lactic Acid polymeric solution and produce fibers that can be used directly on skin with lower side effects and lower dosage when compared to conventional methods of delivering drugs. Morphological, mechanical, thermal, chemical analysis were ivestigated for the fabricated fibers; in addition to swelling antimicrobial, drug release profiles.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)